Librarians' perceptions about adoption and uses of the Koha integrated library software in Punjab, Pakistan. Issue 4 (5th August 2019) - Asim, Muhammad; Mairaj, Muhammad Ijaz
Abstract : Purpose: This study aims to find out the reasons of adopting Koha integrated library software, discovers the problems faced by librarians during its implementation, and gets the perceptions of librarians about the performances of Koha in Punjab, a province of Pakistan. Design/methodology/approach: Survey method was used to collect the data through questionnaire from the purposefully selected sample (N = 66) of university librarians of Punjab, a province of Pakistan. Findings: The librarians adopted Koha due to the availability of Web online public access catalog (OPAC), provision of MARC21 standards for cataloging and its free availability. During implementation, the librarians were faced with the problems of lack of technical skills, lack of knowledge about the Linux operating system, shortage of skilled manpower, slow internet speeds and approval from their organization. They highly rated the performance of the cataloguing, circulation, patron and OPAC modules of Koha. Originality/value: This research provides a brief picture of librarians' perceptions about Koha adoption and satisfaction levels. The findings highlighted the issues and problems faced during the implementation of Koha. This study will be helpful for librarians in the selection, implementation and usage of the Koha software in their libraries.